Antibacterial and synergistic activity of 6β-hydroxy-3-oxolup-20(29)-en-28-oic acid (6β-hydroxy betunolic acid) isolated from Schumacheria castaneifolia vahl. (15th May 2021) - Wickramasingha, W.G.D.; Jayasinghe, S.; Karunaratne, D.N.; Ekanayake, E.W.M.A.; Liyanapathirana, V.; Karunaratne, V.
Graphical abstract: Abstract: Multi- drug resistant microbial pathogens are a serious global health problem and thus new antibacterial agents, which are effective both alone and in combination with traditional antibiotics, are urgently needed. Hence, the objective of the present study was to investigate the antibacterial activity of 6β-hydroxy-3-oxolup-20(29)-en-28-oic acid (6β-hydroxy betunolic acid) isolated from the bark of Schumacheria castaneifolia and its effect when combined with oxacillin. Antibacterial potential of 6β-hydroxy betunolic acid alone was performed using broth micro dilution assay against sixteen bacterial strains which included eight standard strains [ Staphylococcus aureus (ATCC 29213 and ATCC 25923), Enterococcus faecalis (ATCC 29212), Escherichia coli (ATCC 35218 and ATCC 25922), carbapenemase producing Kebsiella pneumonia (ATCC BAA 1705), carbapenemase non-producing K. pneumonia (ATCC BAA 1706) and Pseudomonas aeruginosa (ATCC 27853)] and four strains each of clinically isolated meropenem resistant Acinetobactor sp. and methicillin resistant S. aureus (MRSA) which were included in the urgent threat list and serious threat list, respectively in 2019 by the Centers for Disease Control and Prevention in the United States. Its effect when combined with oxacillin was tested against S. aureus (ATCC 29213) and MRSAs using a checkerboard dilution method. The results indicated that 6β-hydroxy betunolic acid had antibacterial activity against the tested Gram positive organisms with MICs ranging from 16 to 32 mg L −1 (MIC of oxacillin and meropenem ranged from 0.25–16 and 0.03–128 mg L −1 respectively). The high MIC values (>1024 mg L −1 ) of 6β-hydroxy betunolic acid against Gram negative strains indicated a likely lack of activity. Further, 6β-hydroxy betunolic acid exhibited synergistic effect with oxacillin against Staphylococcus aureus (0.49) and showed an additive effect against all the tested MRSAs. The present study suggested that the antibacterial activity of the 6β-hydroxy betunolic acid is restricted to Staphylococcus isolates and possibly Enterococcus faecalis . Further testing on different types of Gram positives and identification of the exact mechanism of action would be of importance.